SEMANTIC INTEROPERABILITY AND CLINICAL TERMINOLOGY STANDARDS IN ELECTRONIC HEALTH RECORDS - Oliveira, Lismary Barbosa de; Braga, Renata Dutra; Provin, Mércia Pandolfo (CIPEEX, 2025)
This study aimed to investigate how clinical standards and terminologies, such as Systematized Nomenclature of Medicine Clinical Terms (SNOMED-CT), Logical Observation Identifiers, Names, and Codes (LOINC), International Classification of Diseases and Related Health Problems (ICD), *International Classification of Primary Care – second edition (ICPC-2)*, Digital Imaging and Communications in Medicine (DICOM), and the Management System of the Procedures, Medications, and Orthoses, Prostheses, and Special Materials Table of the Unified Health System (SIGTAP), contribute to semantic interoperability in Electronic Health Records (EHR) in Brazil and what is the impact of these contributions on the integration and continuity of care in the Unified Health System (SUS). The research was conducted through a bibliographic search, reviewing scientific literature and regulatory documents on clinical terminologies and interoperability standards. The analysis focused on the practical application of each standard and terminology, evaluating their effectiveness in promoting interoperability and improving data quality in EHRs. It was identified that clinical standards and terminologies, such as SNOMED-CT and LOINC, significantly improve semantic interoperability, facilitating the exchange and understanding of data between systems. ICD-10 and ICD-11 help standardize disease coding, while ICPC-2 and DICOM contribute to the classification and communication of clinical data. SIGTAP demonstrates effectiveness in managing SUS procedures. The importance of adopting and integrating clinical terminologies and standards to enhance interoperability in EHRs is highlighted. Overcoming the associated challenges is crucial to improving the continuity and quality of care in SUS.